2002
DOI: 10.1074/jbc.m108912200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of a Troponin I (R145G) Mutation Associated with Familial Hypertrophic Cardiomyopathy

Abstract: Familial hypertrophic cardiomyopathy has been associated with several mutations in the gene encoding human cardiac troponin I (HCTnI). A missense mutation in the inhibitory region of TnI replaces an arginine residue at position 145 with a glycine and cosegregates with the disease. Results from several assays indicate that the inhibitory function of HCTnI R145G is significantly reduced. When HCTnI R145G was incorporated into whole troponin, Tn R145G (HCTnT⅐HCTnI R145G ⅐HCTnC), only partial inhibition of the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 46 publications
10
86
0
Order By: Relevance
“…1A, porcine fibers exchanged and reconstituted with human Tn complex show a decrease in Ca 2ϩ sensitivity (⌬pCa 50 ϭ Ϫ0.14) when compared with untreated fibers. This result is consistent with what was previously observed in our laboratory (17,18). This difference in Ca 2ϩ sensitivity is due to the substitution of human Tn complex into the porcine fibers.…”
Section: Ca 2ϩ Sensitivity Of Force Development In Porcine Skinnedsupporting
confidence: 83%
See 2 more Smart Citations
“…1A, porcine fibers exchanged and reconstituted with human Tn complex show a decrease in Ca 2ϩ sensitivity (⌬pCa 50 ϭ Ϫ0.14) when compared with untreated fibers. This result is consistent with what was previously observed in our laboratory (17,18). This difference in Ca 2ϩ sensitivity is due to the substitution of human Tn complex into the porcine fibers.…”
Section: Ca 2ϩ Sensitivity Of Force Development In Porcine Skinnedsupporting
confidence: 83%
“…The functional consequences of TnT mutations causing FHC have been extensively characterized (12,17,(25)(26)(27). Previously, our laboratory and others have shown that FHC-causing mutations in TnT predominantly increase myofilament Ca 2ϩ sensitivity (12,25,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results demonstrated that most of the FHC-linked cTnI mutations did affect the regulatory processes involving the TnI3 molecule, and that at least five mutations (p.R145G, p.R145Q, p.R162W, K183del, and p.K206Q) increased the Ca 2ϩ sensitivity of cardiac muscle contraction (Takahashi-Yanaga et al 2001). The R145G mutation has been shown to result in severe diastolic dysfunction and somewhat decreased contractility leading to hypertrophy as a compensatory mechanism (Lang et al 2002). The K183del is the most common mutation found in this gene.…”
Section: Troponin I (Tni3) Genementioning
confidence: 99%
“…cTn I is only expressed in cardiomyocyte, and is not expressed in the skeletal muscle. Therefore, cTn I is the antigen of cardiomyocyte specificity (Lang et al, 2002). This experiment used BrdUrd labelling transplant cell and sites at the cell nucleus, used cTn I as the specificity antigen of cardiomyocyte and sites at cytoplasm.…”
Section: Discussionmentioning
confidence: 99%